El Mariachi [videorecording (DVD)] - Rodriguez, Robert, 1968-; Rodriguez, Robert, 1968-; Gallardo, Carlos; Gómez, Consuelo; Martínez, Reinol; Marquardt, Peter (Actor); Trujillo, Marc Allen (Mexico trilogy., 2003)
"All he wants is to be a mariachi, like his father, his grandfather and his great grandfather before him. But the town he thinks will bring him luck brings only a curse of deadly mistaken identity. Forced to trade his guitar for a gun, the mariachi is playing for his life"--Container